Agent for the resistance : a Belgian saboteur in World War II - Bodson, Herman, 1912- (Texas A & M University military history series ;, 1994)
As German presure on Europe escalated in the late 1930s, a young Belgian pacifist completing his Ph. D. in chemistry watched with horror the preparation for the inevitable invasion of his country. In the face of advancing German troops, his passion for freedom and his growing hatred of Hitler led him and a group of friends into the resistance movement and five years of privation, danger and, for some, torture and death at the hands of the Gestapo.